2021
DOI: 10.1088/2053-1591/ac3042
|View full text |Cite
|
Sign up to set email alerts
|

Sputter deposition of Mo-alumina cermet solar selective coatings: Interrelation between residual oxygen incorporation, structure and optical properties

Abstract: Mo/alumina cermet-based selective coatings are of great interest for concentrated solar-thermal power systems, in particular, parabolic trough collectors. We report on the sputter deposition of high-performance multilayer Mo/alumina cermet coatings on stainless steel with a solar absorptance of 94% and a thermal emittance of 8% (at 400 °C), and excellent thermal stability. The selective coatings were deposited in a 0.95 m3 sputtering chamber in order to correlate the deposition parameters, such as presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…28 A thin Mo overlayer was deposited by RF sputtering onto the TiO 2 -coated FTO substrates using a rectangular magnetron sputtering gun (Gencoa SW50200) and a rectangular Mo target (5 cm × 20 cm) of a purity of 99.95%. The optimized sputtering parameters corresponded to an RF power density applied to the target of 6 W cm −2 and an argon pressure in the chamber of 0.3 Pa, following the procedure described by Becerril-Gonzalez et al 29 The metallic Mo overlayer was oxidized using the following heating ramp program: starting at room temperature, the temperature was increased by 100 °C steps each hour until reaching 600 °C where the temperature was maintained for 1 h, allowing to cool to room temperature after deposition. XRD grazing angle studies showed the presence of a molybdenum oxide, MoO x , in composition close to MoO 3 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…28 A thin Mo overlayer was deposited by RF sputtering onto the TiO 2 -coated FTO substrates using a rectangular magnetron sputtering gun (Gencoa SW50200) and a rectangular Mo target (5 cm × 20 cm) of a purity of 99.95%. The optimized sputtering parameters corresponded to an RF power density applied to the target of 6 W cm −2 and an argon pressure in the chamber of 0.3 Pa, following the procedure described by Becerril-Gonzalez et al 29 The metallic Mo overlayer was oxidized using the following heating ramp program: starting at room temperature, the temperature was increased by 100 °C steps each hour until reaching 600 °C where the temperature was maintained for 1 h, allowing to cool to room temperature after deposition. XRD grazing angle studies showed the presence of a molybdenum oxide, MoO x , in composition close to MoO 3 .…”
Section: Experimental Methodsmentioning
confidence: 99%